Linked Data, JSON-LD and the Semantics of Cultural and Scientific Heritage - Ovidiu Turcoane (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
This paper discusses the importance of linked data for the semantics of cultural and scientific heritage and it provides some reasons on using JSON- LD as a standard. From a conceptual point of view, cultural and scientific heritage should widen for broad human and computer access. Web semantics support the transformation of information to knowledge on a large and open scale and cultural and scientific heritage should benefit from that, especially if we see the latter as a pillar in a lean system, such as E-Democracy that seeks for permanent improvement. Cultural and scientific heritage has a primary role in education of individuals but also in the optimization process of knowledge society through the humane collective approach of trial and error. In order to build a society of inclusion using vertical (temporal) and horizontal (spatial) inquiries in social values, religions, beliefs and rituals we must facilitate broaden and less restrictive access. One way to achieve this task is by using linked data for connectivity and meaning of information and the standard of JSON-LD for extensive and simple digital access.